LZTS2 inhibits PI3K/AKT activation and radioresistance in nasopharyngeal carcinoma by interacting with p85. (28th April 2018) - Xu, Shuangbing; Li, Yan; Lu, Yanwei; Huang, Jing; Ren, Jinghua; Zhang, Sheng; Yin, Zhongyuan; Huang, Kai; Wu, Gang; Yang, Kunyu
Abstract: Phosphoinositide 3-kinase (PI3K) activity is aberrantly activated in nasopharyngeal carcinoma. However, the underlying mechanisms remain unclear. Here, we found that Leucine zipper tumor suppressor 2 (LZTS2) was downregulated and predicted poor prognosis in nasopharyngeal carcinoma patients. Furthermore, we identified the PI3K subunit p85 as a novel LZTS2-interacting protein using an unbiased proteomics approach. Moreover, we demonstrated that LZTS2 competes with p110 for p85 binding and inhibits activation of the PI3K/AKT signaling pathway. Functionally, we showed that LZTS2 suppresses tumorigenesis and radioresistance in nasopharyngeal carcinoma in a p85-dependent manner. Taken together, our results not only provide understanding of the molecular mechanisms by which PI3K/AKT signaling is activated but also suggest that targeting the LZTS2/PI3K/AKT signaling axis is a promising therapeutic strategy for radiosensitization of nasopharyngeal carcinoma. Highlights: LZTS2 is downregulated and predicts poor prognosis in NPC. LZTS2 interacts with p85 to inhibit activation of the PI3K/AKT signaling pathway. LZTS2 suppresses tumorigenesis and radioresistance in NPC cells in a p85-dependent manner.